Eficacia del proceso de sucesión en empresas familiares vinculadas a la mediana minería formal peruana - Schwarz Díaz, Max (2016)
Research proposes an effectiveness measurement about succession towards the medium Peruvian mining companies through an evaluation of the market value change of the company group represented. Twelve company groups cases were reviewed and 85 Peruvian familycorporate companies related to the medium formal mining industry during the 2000-2015 period, in which up to four categories were found as part of the value change that presents different context conditions about focus change and company direction as a result of the succession in charge. The results show exchange rates in the market value of (>10%) as consequence of succession process for the family companies’ cases where the change was professionally prepared to take over the leadership of the company; exchange rates in the range of 5% to 10% for cases where the second generation had not followed a process of professionally planned preparation of succession; and lower change rates of 5% for cases where the succession corresponds to the coexistence in the management of the various activities of the company between patriarch and successor(s).